Cross-sectional area and mean echogenicity of shoulder and elbow tendons in adult German Shepherd dogs - Spinella, G.; Loprete, G.; Musella, V.; Britti, D.; Vilar, J. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
The aim of this study was to describe the cross-sectional area and mean echogenicity of the main tendons of the shoulder and elbow joints in adult German Shepherd dogs and to determine the effects of sex, weight, and age on these parameters. No previous publications in the veterinary literature have reported information regarding quantitative ultrasonographic tendon measurements in dogs.Thirty German Shepherd dogs were examined: 13 males and 17 females. The cross-sectional area was significantly higher in males than in females (p <0.05) for the distal tendon of the triceps brachii muscle and the tendons of the flexor carpi ulnaris and common digital extensor muscles. The influence of sex on mean echogenicity was not significant. According to age, mean echogenicity was higher in older dogs, while the cross-sectional areas were similar in the two groups. Cross-sectional area and mean echogenicity of the tendons showed a direct increase with an increase in body weight. The data gained from this study can help support the clinician to discriminate between normal and pathological conditions.
Keywords: Cross-sectional area; mean echogenicity; tendon; shoulder; elbow; dog